Netralitas Aparatur Sipil Negara dalam Pemilihan Umum: Studi Penegakan Hukum - Jacobus Ronald Mawuntu; Jemmy Sondakh; Patria Caraka Regar (Al-Ishlah: Jurnal Ilmiah Hukum, 2022)
This study aims to analyze law enforcement related to ASN Neutrality in the elections at the national and regional levels based on laws and regulations. This study uses a normative juridical method. The collection of primary, secondary, and tertiary legal materials is carried out using literature study techniques. The collected legal material is then analyzed using qualitative data analysis methods with a statute approach. The results show that the law enforcement related to ASN Neutrality in the elections at the national and regional levels consists of Law No. 5 of 2014, Law No. 7 of 2017, Law No. 6 of 2020, and Government Regulation No. 94 of 2021. Servants proven to have committed violations related to ASN neutrality will be imposed disciplinary and criminal punishment. In this case, the disciplinary punishment levels consist of moderate or severe. At the same time, the most severe criminal punishment is imprisonment for 24 (twenty-four) months and/or fines of IDR 1,000,000,000.00 (one billion rupiahs). In contrast, if ASN Servants are proven to have committed violations but are not followed up, then KASN recommends to the President to punish PPK/Executors/Officials and Authorized Officials by the provisions of laws and regulations. Therefore, it is recommended that the ASN Servants Neutrality Supervising Task Force monitors and evaluates the follow-up results of KASN recommendations. Furthermore, it is necessary to impose strict punishment on Servants who violate the provisions regarding the neutrality of ASN to make the bureaucracy clean from abuse of authority during future elections.